Remarks on Xylomedes Lesne, 1902 with description of a new species from Iran (Coleoptera: Bostrichidae, Apatinae) - Jerzy, Borowski; Andrzej, Lasoń; Marek, Sławski (Zootaxa, 2021)
Xylomedes bidasi n. sp., hitherto known only from Iran, is described as a new species. X. turcica Lesne is considered a junior synonym of X. cornifrons (Baudi), and X. rufocoronata (Fairm.) n. stat.—a subspecies of X. cornifrons. A key to the identification of Asian representatives of the genus Xylomedes Lesne is provided, as well as an updated catalogue of all known species with their geographical distribution.